2000
DOI: 10.1088/0022-3727/33/20/201
|View full text |Cite
|
Sign up to set email alerts
|

Surface analytical science and automotive lubrication

Abstract: This paper discusses the role surface analytical science has played in understanding the complex phenomena occurring during lubrication of modern internal combustion engines. The interactions between the multi-functional lubricant additives and the various metallic surfaces present in the tribological contacts are complex and lead to the formation of inhomogenous multi-layer protective surface films. Surface analysis by ultra-high vacuum (UHV) techniques such as x-ray photoelectron spectroscopy, Auger electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…While ZDDP tribofilms can be formed between other non-ferrous material pairs, e.g., low-friction diamond-like carbon (DLC) films, they are often less durable than those formed when steel or iron is present for reasons not yet understood (9,10). It is desirable to reduce or replace ZDDP as it often increases frictional losses (3), and produces Zn-, Pand S-containing compounds in the exhaust, reducing the catalytic converterÕs efficiency and lifetime (1,3,11,12). Despite decades of research, no suitable substitute for ZDDP has yet been found (12), motivating research to understand the beneficial mechanisms underlying the growth and antiwear properties of ZDDP-derived tribofilms.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…While ZDDP tribofilms can be formed between other non-ferrous material pairs, e.g., low-friction diamond-like carbon (DLC) films, they are often less durable than those formed when steel or iron is present for reasons not yet understood (9,10). It is desirable to reduce or replace ZDDP as it often increases frictional losses (3), and produces Zn-, Pand S-containing compounds in the exhaust, reducing the catalytic converterÕs efficiency and lifetime (1,3,11,12). Despite decades of research, no suitable substitute for ZDDP has yet been found (12), motivating research to understand the beneficial mechanisms underlying the growth and antiwear properties of ZDDP-derived tribofilms.…”
Section: Main Textmentioning
confidence: 99%
“…Direct experimental evidence for this model is lacking (3), and it does not explain tribofilm formation on non-ferrous surfaces (6,7). In contrast, Mosey et alÕs first principles atomistic simulations proposed that tribofilm formation results from contact pressure-induced cross-linking of zinc phosphate molecules (8) which are a thermal or catalytic decomposition product of ZDDP (11,15). Overall, there is no consensus on the growth mechanism, and no models conclusively explain either the tribofilm patchiness or why the film thickness is limited.…”
Section: Main Textmentioning
confidence: 99%
“…Their presence in the bulk of the deposit, but not near the deposit/substrate interface, suggests their formation during the normal operating temperature period of the engine tests and is in agreement with a growth mechanism based on thermal degradation and oxidation. 18 The fine structure of the deposit was found to be contained within a matrix consisting of a mix of calcium sulphates, zinc phosphates, organic material and possibly calcium carboxylates. These compounds are likely to have formed from thermal and oxidative degradation of the lubricant film to give a concentration of additive species in a gum-like material consisting of the less-volatile components of the original base oil.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature of 150°C is sufficient to cause thermal decomposition of the ZDDP molecule, giving rise to both oil-soluble components, such as organic sulphides and organothiophosphates, and oil-insoluble components, such as zinc polyphosphates. 18 It is these oil-insoluble components that are most likely to have contributed to the initial stages of deposit formation. These initial layers were found to be ¾50 nm in total thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The most common, and the best antiwear additive used in engine oils today is zinc dialkyl-dithiophosphates (ZDDPs; figure 1). Extensive reviews of its formation, composition, and performance can be found in references [14][15][16][17][18]. The antiwear film is formed of an agglomeration of patches (termed antiwear pads) that are raised from the surface by up to 400 nm.…”
Section: Introductionmentioning
confidence: 99%